Analogical Pedagogy for Control Systems: A Case Study on Controllability and Observability - Munje, Ravindra; Beldar, Pankaj; Joshi, Ajinkya; Rakibe, Priya (Journal of Engineering Education Transformations, 2026)
This study investigates the effectiveness of analogy-based pedagogy in enhancing the understanding of the abstract concepts of controllability and observability in a Control Systems course. Two analogies—one based on a car driving scenario and another on the teaching–learning process—were introduced sequentially to a cohort of 120 undergraduate electrical engineering students. Performance was assessed using a structured pre-test and two post-tests following each analogy session. Statistical analysis, including paired t-tests, F-tests for variance, and ANOVA, revealed significant improvements in student scores after each analogy intervention, with stable score variability, indicating genuine comprehension gains. Qualitative feedback further supported the positive impact of the analogies on student engagement and conceptual clarity. These results demonstrate that carefully crafted analogies serve as effective instructional tools to bridge the gap between abstract theory and intuitive understanding in engineering education.